The new self-directed work teams mastering the challenge - Orsburn, Jack D. (Self-directed work teams, 1999)
"The New Self-Directed Work Teams, Second Edition, explores the latest work team implementation guidelines, provides dramatic case studies of the positive impact of self-directed work teams, and discusses the surprising trends and market realities that are redefining the employer/employee relationship as we enter the 21[superscript st] century."--Jacket.